Impact of Stroke Risk Factors on Ethnic Stroke Disparities among Midlife Mexican Americans and Non-Hispanic Whites - Patel, Rajiv C. (Stroke, 2017)
BACKGROUND AND PURPOSE: We examined the contribution of stroke risk factors to midlife (age 45–59) Mexican American (MA) and non-Hispanic White (NHW) ischemic stroke (IS) rate disparities from 2000–2010. METHODS: Incident IS cases (N = 707) and risk factors were identified from the BASIC Project, Nueces County, Texas (2000–2010). US Census data (2000–2010) was used to estimate the population at-risk for IS, and the Behavioral Risk Factor Surveillance System (2000–2010) was used to estimate risk factor prevalence in the stroke free population. Poisson regression models combined IS counts (numerator) and population at-risk counts (denominator) classified by ethnicity and risk factor status to estimate unadjusted and risk factor adjusted associations between ethnicity and IS rates. Separate models were run for each risk factor and extended to include an interaction term between ethnicity and risk factor. RESULTS: The crude rate ratio (RR) for ethnicity (MA vs. NHW) was 2.01 (95% CI: 1.71, 2.36), and was attenuated in models that adjusted for diabetes (RR: 1.50, 95% confidence interval (CI): 1.26, 1.78) and hypertension (RR:1.84, 95% CI: 1.50, 2.26). Additionally, diabetes had a stronger association with IS rates among MAs (RR: 6.42, 95% CI: 5.31, 7.76) compared with NHWs (RR: 4.07, 95% CI: 3.68,4.51). CONCLUSIONS: The higher prevalence of diabetes and hypertension and stronger association of diabetes with IS among midlife MAs likely contribute to persistent midlife ethnic stroke disparities.